PERJUANGAN PEREMPUAN DALAM NOVEL BATAS KARYA AKMAL NASERY BASRAL( KAJIAN FEMINISME) - Christia Tasiana; Martono Martono; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to increase the reader's understanding of women's struggles in the novel Batas by Akmal Nasery Basral. The theory used in this research is feminism. This study uses a descriptive method, a form of qualitative research. The data source in this research is the novel Batas by Akmal Nasery Basral. The data collection technique in this research is a documentary study technique. The data in this study are in the form of quotes from words, phrases, sentences containing a form of struggle carried out by the main female character. The results showed that the data obtained amounted to 12 data. The struggle in the field of education is obtained, namely, the struggle to teach, the struggle to motivate, the struggle to be responsible. The struggle in the economic field was obtained, namely, the struggle to obtain donations for border economic development. The struggle in giving opinions is obtained, namely, the struggle to be accepted in society, the struggle to be respected by fellow co-workers. The implementation plan for learning the results of this study is combined with Indonesian language learning in class XII SMA level in the 2013 curriculum with KD 3.1 understanding the structure and rules of the novel text, both through oral and written and KD 4.1 interpret the meaning of the novel text both orally and in writing. Indicator 3.1.1 determines the structure of the novel text. 3.1.2 determine the rules/language characteristics of the novel text. 4.1.1 interpret of the novel text both orally and in writing.Keyword: Feminism, Novel, Struggle.